Pengembangan Media Ular Tangga Truth Or Dare Budaya Lokal Pada Pembelajaran IPS Kelas IV Di SDN 8 Banyuasin II - Silvy Shaleha Yulianti; Lukman Hakim; Kiki Aryaningrum (CV. ITTC INDONESIA, 2024)
The aim of this research is to produce truth or dare snakes and ladders media for local culture in social studies learning for grade IV elementary schools that is valid, practical and effective. The research method used is RnD with a 4D development model. To obtain data, researchers used several data collection techniques, namely interviews, expert assessments, questionnaires and tests. The data that has been collected using the instruments above is then used to describe the assessment of the quality of the snakes and ladders learning media on the material on ethnic and religious diversity in my country in class VI elementary school based on valid, practical and effective criteria. The data is analyzed using questions from the problem formulation. Based on the trial, it showed that the truth or dare snakes and ladders media received a positive response from students. In the one to one trial, the student response showed a percentage of 87.5%, while in the small group trial, the student response showed a percentage of 83.7%. Based on the validation results from the 4 validators, material experts, media experts and media linguists, Snake and Ladder, Truth or Dare was declared